2017
DOI: 10.1002/eat.22767
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic CRF1 receptor mechanisms are not sufficient to account for binge‐like palatable food consumption in female rats

Abstract: Rationale The interaction between dieting and stress is a key factor for triggering binge episodes on palatable food in human binge eaters. Corticotropin releasing factor (CRF) mechanisms are known to play a pivotal role in the regulation of this maladaptive behavior. Objective The present study evaluated the effect of systemic injection of the CRF1 receptor antagonist R121919, the corticosterone synthesis inhibitor metyrapone and central amygdala (CeA) injections of the nonselective CRF antagonist D-Phe-CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 68 publications
(105 reference statements)
2
16
0
Order By: Relevance
“…In agreement with this notion, and overlapping with the trend of c-Fos induction in the AMY, we found that OEA decreased CRF mRNA level in the CeA of R + S rats, without producing any effect on the PVN, and without affecting the same parameters in NR + S rats. The results confirm previous findings demonstrating that hypothalamic CRF system is not sufficient to account for binge-like HPF consumption in our BED model [ 47 , 48 ], and that CRF in the CeA plays a key role in other models of excessive palatable food consumption [ 67 69 ]. These latter observations were further supported by the findings that treatments with CRF antagonists can prevent binge eating by interacting with CRF receptors in bed nucleus of the stria terminalis [ 47 , 48 , 70 ] and CeA [ 67 69 ], rather than at hypothalamic levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with this notion, and overlapping with the trend of c-Fos induction in the AMY, we found that OEA decreased CRF mRNA level in the CeA of R + S rats, without producing any effect on the PVN, and without affecting the same parameters in NR + S rats. The results confirm previous findings demonstrating that hypothalamic CRF system is not sufficient to account for binge-like HPF consumption in our BED model [ 47 , 48 ], and that CRF in the CeA plays a key role in other models of excessive palatable food consumption [ 67 69 ]. These latter observations were further supported by the findings that treatments with CRF antagonists can prevent binge eating by interacting with CRF receptors in bed nucleus of the stria terminalis [ 47 , 48 , 70 ] and CeA [ 67 69 ], rather than at hypothalamic levels.…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated a crucial role of oxytocinergic neurotransmission in mediating the hypophagic effect of OEA [ 29 ], as well as the pivotal role played by CRF system in sustaining binge eating behavior in the experimental model used in the present study [ 47 ]. Since both oxytocin and CRF can be affected by stress and food intake, we assessed the “pure” effects of OEA on stress response without the potential impact of caloric consumption, to evaluate whether the anti-bingeing effects of OEA might be attributed to a reduced effect of stress exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RXFP3 activation in the PVN is necessary for the occurrence of BE behavior RLN3/RXFP3 signaling has been linked to binge-like eating (Lenglos et al, 2013;Calvez et al, 2016b); so to further assess the involvement of PVN RXFP3 in this phenomenon, we used an established rat model of BE (Cifani et al, 2009;Piccoli et al, 2012;Micioni Di Bonaventura et al, 2017) combined with intra- Figure 4. NI RLN3 neurons innervate the PVN and its adjacent areas, with a higher fiber density in female than in male rats.…”
Section: Rxfp3-a2mentioning
confidence: 99%
“…Indeed, frustration stress manipulation increased BNST neuronal activity and CRF receptors of BNST seem to have a critical role in stress-induced binge eating disorder [ 201 ]. The role of other extra-hypothalamic CRF1 receptors, as those in central amygdala, has been also implicated in development of binge eating [ 202 ]. The early emotional environment also impacts on eating behaviour.…”
Section: Binge Eating Disorder a “Full-fledged” Pathologymentioning
confidence: 99%